The Application of Numbered Heads Together (NHT) in Online Learning - Febrian Solikhin; Weni Inda Sari; Krisna Dewi (International Journal of Chemistry Education Research, 2021)
This research is a Classroom Action Research conducted at Public Senior High School 3 Bengkulu City, especially class XI MIPA 4. Online learning in this class reduces student learning activities. Many students are passive in learning. This affects decreasing their learning outcomes. For that, it is necessary to provide the appropriate treatment for solving the problem. This treatment is to apply a learning model that requires students to be more active in learning. One of them is the Numbered Head Together (NHT) learning model. This study aims to increase student activeness in the online learning process and improve student learning outcomes using the NHT model, especially chemical equilibrium material. The subjects of this study were 34 students of class XI MIPA 4. The instruments used were the student activeness observation sheet and the learning outcome test instrument. This research runs in 2 cycles, with each cycle consisting of planning, implementing, observing, and reflecting. The results obtained, overall, there was an increase in student activity in the online learning process and student learning outcomes. The percentage of student activeness in online learning increased from 40.19% in cycle I to 85.29% in cycle II. Meanwhile, the percentage of student learning outcomes completeness was risen from 55.88% in the first cycle to 82.35%. Both have achieved the target set, which is 75%.